Comparison of vineyard-associated Saccharomyces cerevisiae populations by microsatellite analysis - Valero, Eva (2006)
The aim of the present study was to evaluate populational structures among fermenting S. cerevisiae populations. Analysis of six polymorphic microsatellite loci was performed in 468 S. cerevisiae isolates derived from a previous screening (using mtDNA RFLP or electrophoretic karyotyoing) of 2490 yeast strains obtained from spontaneous fermentations of grapes collected in three vineyards of the Vinho Verde Region (northwest Portugal), and one vineyard of the Languedoc Region (South France) during the 2001 – 2003 harvest seasons. Among the 93 alleles obtained, 52 new alleles were identified. For all loci analyzed, observed heterozygosity was three to four times lower than the expected value, probably due to a strong populational substructuring. Populational structures were identified based on the accumulation of small allele-frequency differences across six loci in groups of strains. The present work is the first large-scale approach showing that microsatellite typing reveals a very fine population resolution of indigenous S. cerevisiae strains isolated from vineyards.